Jurnalisme Kampus: Sistem Penugasan Dan Pola Komunikasi Pers Mahasiswa UINSA Surabaya - Fikry Zahria Emeraldien; Alfina Nurhayati; Choe Rotuzzakia; M. Ianur Rofi' (Jurnal Ilmu Komunikasi, 2022)
The existence of a student press institution at a university, through which the students can enhance their creativity with regard to journalism as well as a laboratory for students of the department of communication and broadcast, is pivotal. UIN Sunan Ampel Surabaya has campus press and broadcasting institutions, such as campus television, radio, tabloids, and bulletins. This research seeks to examine the communication patterns of journalists and the professionalism of the assignment system within the student press institution at UIN Sunan Ampel Surabaya. Using an ethnographic approach, this study has found that there are similarities in the news production system of student press with professional press institutions. Meanwhile, the communication pattern of the student press organization is multi-directional with a strong sense of brotherhood